Teores dos elementos químicos essenciais e tóxicos na rastreabilidade da carne bovina - Gromboni, Caio Fernando (Universidade Federal de São Carlos, 2012)
The objective of this work was to develop methodologies for the determination of inorganic constituents in meat sample and the study of correlations between samples with chemical elements profile, especially Nelore samples of project BifeQuali aimed at improving the quality of Brazilian meat. Three different strategies for sample preparation, basic extraction, acid extraction and microwave assisted acid digestion were optimized and evaluated, by using bovine liver certified reference material (NIST 1577b), and the decomposition assisted by microwave radiation chosen for the decomposition of 650 samples used in this work. For the measurements of chemical elements, mass spectrometry and optical emission inductively coupled argon plasma (ICP OES and ICP-MS, respectively) were used. The chemical elements quantified by ICP-MS were V, Mn, As, Co, Ni, Mo, Cd, Pb, Cr, Se and Fe, by ICP OES were Ca, K, Mg, Na, P, S and Zn. The use of internal standard (Sc, Y and Bi) contributed to the accuracy and precision of measurements. For principal component analysis (PCA) was developed a worksheet to perform the spectral scanning, monitoring 250 wavelength from 167 to 770 nm using ICP OES. The results showed that the crop that is bred proved to be an important variable, forming clusters corresponds to the two crops analyzed, which indicates that climatic factors affect the profile of chemical elements and the quality of nutrition. Moreover, the place of confinement is also presented as an important variable, showing the grouping according to the place where it was confined. Through PCA and analysis using SAS software was possible to observe the correlation between Na and K with the tenderness, and the higher the concentration of these, the lower the shear force, and the higher the tenderness
Levels of essential and toxic chemical elements of traceability in beef
Keywords: Química analítica; Preparação de amostra (Química analítica); ICP-MS; Quimiometria; Carne bovina; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA